Implementasi Algoritma Greedy pada Pewarnaan Wilayah Peta Kecamatan Gelumbang Muara Enim - Al Jufri, Khuzaimah; Agustiani, Riza (Diophantine Journal of Mathematics and Its Applications, 2023)
A map becomes more attractive and easier to read when it is colored. However, excessive use of color can make the map ineffective. Gelumbang Subdistrict was chosen because its map had not yet been colored. Graph theory can be applied to the problem of map region coloring. Gelumbang Subdistrict is represented by a dual graph consisting of 23 vertices and 53 edges. The Greedy Algorithm was chosen as the solution to the coloring optimization problem for the Gelumbang Subdistrict map, resulting in a minimum coloring that uses four colors to represent all 23 villages within the subdistrict.